Small RNA or oligonucleotide drugs and challenges in evaluating drug-drug interactions - Cronin, Joseph M.; Yu, Ai-Ming (Frontiers in Pharmacology, 2025)
Small RNA or oligonucleotide therapeutics represent a unique modality outside the traditional treatment paradigm of small molecule and protein-based drugs that have historically only targeted a small fraction of the proteome. Innovations in the structural design and chemical modification have been invaluable for recent oligonucleotide therapeutics, greatly improving their biological stability, intracellular delivery, and targeting. Widespread adoption of these strategies has further enabled the application of oligonucleotides as viable drugs and expanded the class of RNA therapeutics, with thirteen antisense oligonucleotides (ASOs) (fomiversen, mipomersen, nusinersen, inotersen, eteplirsen, golodirsen, casimersen, viltolarsen, tofersen, eplontersen, olezarsen, and donidalorsen), seven small interfering RNAs (siRNAs) (patisiran, givosiran, lumasiran, inclisiran, vutrisiran, nedosiran, and fitusiran), and two aptamers (pegaptanib and avacincaptad pegol) that have been approved by the United States Food and Drug Administration (FDA). RNA therapeutics have expanded the druggable space and provide a novel treatment strategy, they do not fit within the framework of our current methodology in evaluating risk of drug-drug interactions (DDIs) and assessing pharmacokinetic/pharmacodynamic (PK/PD) relationships. This article provides an overview of FDA-approved oligonucleotide therapies, emphasizing chemical modifications, molecular targets for mechanistic actions, and available ADME and PK/PD properties, followed by the discussion of critical needs for risk assessment strategies suited for this unique modality that focuses on possible DDIs with concomitant drugs. The latter may involve direct competition for the endogenous RNA interference machinery to alter ADME or relevant PD gene expression, rather than uncommon binding or interactions with drug-metabolizing enzymes or transporters found and recommended for small molecule drugs.